The structure of fish community in the river Mirna - Jakopin, Jasmina (Acta biologica slovenica, 2012)
Natural perturbations and human pressure increasingly affect the river ecosystems and their biological communities. Fish species are a good indicatorof the river status and one of the factors for the assessment of ecological condition by the Water Framework Directive (Directive 2000/60/EC). River Mirna, one of the larger right tributaries of the river Sava, is a good example of anthropogenic pressure on the running water ecosystem. Fish community species structure was analyzed at selected eight sampling sites located over the 28 km length of the river. Abiotic conditions were determinedby measuring the physical, chemical and hydro-morphological parameters and the influence of measured parameters on present fish community was analyzed. It has been determined, that the river Mirna is loaded with organic matter and physically changed by regulations, river beds canalizing and bank stabilization. Fish were sampled with standard electro-fishing methodto determine species diversity, biomass of the specimens and their size.29 fish species from seven families (26 native and 3 allochthonous species) were recorded along with one type of the Danubian brook lamprey (Eudontomyzon vladykovi). Only two species, Telestes souffia and Cottus gobio,were present at all eight sampling sites. The largest number of specimens (890) and the largest biomass (5697 g) per 100 m2 was recorded at the sampling site located after the town as a result of the flow of purified water from the water treatment plant and a large number of invertebrates, which are an important food source. The minimum number of specimens per 100 m2(86) and the minimum biomass of fish per 100 m2 (457 g) was measured at the relatively natural part of the channel. The most common causes for this are low temperatures, less food and a fast, turbulent flow. The study confirms that the changes in abiotic factors induced by anthropogenic activities significantly influence the structure of fish species community.
Keywords: anthropogenic pressure; antropogeni vplivi; diverziteta ribjih vrst; fish biodiversity; fish community; loading; obremenjevanje; running waters; tekoče vode; združba rib